Relationship between Perceived Social Support and Adherence to Medical Advices among Patients with Coronary Heart Disease after By-pass Surgery - Montazer; Foroozannia; Masoudnia (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2012)
Introduction: The aim of this study was to determine the relationship between perceived social support and adherence to medical advices among patients with heart disease after by-pass surgery in Yazd. Methods: This study was performed with a survey design and cross- sectional method. Data were collected from 75 patients with coronary heart disease after by-pass surgery in Afshar hospital in Yazd. The instruments of data collection were Perceived Social Support(SSS) and Adherence to Medical Advices Questionnaire. Results: There was a significant correlation between perceived social support(P<0.01), perceived support by significant others(P<0.05), and perceived support by family(P<0.05) and adherence to medical advices among patients with heart disease. Hierarchical multiple regression analysis showed that the social-demographic variables(step 1) explained 9.9% and perceived social support(step2) explained 5.8% of the variance in adherence to medical advices. Conclusion: The results showed that perceived social support variable affects adherence to medical advices. Therefore, to reinforce the adherence to medical advices among patients with coronary heart disease it seems necessary to attend to social support in behavioral interventions.